The rise of tech and the question of power: a review on detection and classification of multiple power quality disturbances / Mohd Saiful Najib Ismail @ Marzuki ... [et al.] - Ismail @ Marzuki, Mohd Saiful Najib; Abidin, Ahmad Farid; Jusoh, Mohd Zamri; Johari, Dalina (UiTM Press, 2023)
Every single device responds differently to each disturbance, in addition, electrical devices themselves, at times, cause PQ disturbance. Recent studies are focussed on signal processing and classification method of PQ disturbances. The aim of the study is to find the best combination method of classifying multiple PQ disturbances. 80 papers were reviewed in this study. The papers are grouped into several categories related to signal processing and classification method. In this study, an Excel spreadsheet was used to outline the strengths and the weaknesses of the classification methods disscussed in the papers. It is found that the close similarity of characteristic hinders quality detection of PQ disturbance and secondly, previous researchers have chosen limited features extraction hence the lack of information for performing detection. Therefore, a development of modified methodologies is needed in improving the robustness in features extraction and better performance of PQ disturbances classifier. For future studies, it is suggested to focus on Stockwell Transform and Support Vector Machine combination in the methodology.